Bush in Babylon : The Recolonisation of Iraq - Tariq Ali (Rawalpindi Army Education Press, 2005)
The radical colonels, courageous communists and burnt-out Ba'athists failed to establish a stable and just democratic republic, thus enabling a return visit by imperialism
Include Illustration and Index
Keywords: Iraq -- Iraq War (2003-2011) -- United States